Accessibility of Peripheral Regions: Evidence From Aegean Islands (Greece) - Ioannis Spilanis; Thanasis Kizos; Paraskevi Petsioti (Island Studies Journal, 2012)
Islands, especially smaller ones, are characterized by discontinuity of space and are considered as some of the least accessible areas. In this paper, we seek to shed light on the accessibility problems that islands face from the point of view of island residents. This shift in emphasis considers additional aspects to accessibility that include the availability of connections to access services required to cover the needs of island residents and the different destinations where these may be available, and the time that one may have to spend to get to these destinations in order to use these services. An alternative measure of accessibility is proposed, based on the time required to travel; this is then applied to three different Greek islands in the Aegean Sea. The accessibility of the residents of these islands to selected services is compared with that of settlements in continental Greece of similar population and distance to the capital Athens. The findings clearly demonstrate the adversities that island residents have to face, especially for smaller islands, where accessing selected services may require as many as four destinations, with virtual distances 4 to 6 times longer than ‘real distances’.